An alpha7 nicotinic acetylcholine receptor agonist induces retinal neurogenesis and restores electrophysiological function following blast-induced ocular trauma in adult mice - Nolasco de Carvalho, Giovanna V.; Spitsbergen, Jake B.; Linn, David M.; Linn, Cindy L. (Frontiers in Neuroscience, 2025)
IntroductionBlast-induced ocular trauma is a major cause of vision loss in both civilian and military populations and effective treatments are limited by the adult mammalian retina’s inability to regenerate neurons lost to injury or aging. This study evaluated the neurogenic potential of PNU-282987, an alpha7 nicotinic acetylcholine receptor agonist, in an adult mouse model of blast-induced retinal trauma. We tested whether a delayed treatment paradigm, initiated after substantial neuronal loss occurred, could induce neurogenesis and restore retinal function.MethodsAdult mice received a single blast exposure, resulting in a significant reduction in cell counts across all retinal layers and decreased electroretinogram (ERG) amplitudes. One month after injury, when neuronal loss was fully established, daily eye drops of PNU- 282987 were administered for two weeks. Neurogenesis and cellular proliferation were assessed using BrdU incorporation and co-labeling with retinal ganglion cell and photoreceptor markers. Retinal function was evaluated with ERG recordings, and cell counts in treated retinas were compared with untreated blasted eyes and uninjured controls.ResultsDelayed PNU-282987 treatment induced robust cellular proliferation and neurogenesis throughout the retina. Treated retinas showed significantly increased retinal ganglion cell and photoreceptor counts compared with untreated blast-injured eyes, reaching levels not significantly different from control retinas. Electrophysiological analysis revealed a significant recovery of ERG amplitudes, returning to baseline levels in most cases.Discussion/ConclusionThese findings demonstrate that PNU-282987-induced neurogenesis is sufficient to restore retinal structure and function even when treatment is initiated one month after blast injury. This work establishes a promising novel therapeutic approach for treating retinal trauma in adults.